(untitled) (Malay Literature, 2019)
This article aims to highlight the changes in Sabah Malay literature by scrutinizing the changing thematic treatment and narrative styles in a selected number of short stories published in the literary magazine, Wadah, which are strategically published from the 1980s until today. Wadah is a Malay literary magazine that was initiated by Dewan Bahasa dan Pustaka Sabah in 1986 and is designed to encourage the growth of the Malay language and literature. Through a critical analysis of the narrative styles of six short stories-namely Azmah Nordin’s "Lumbai" (1987), Jonathan Kandok’s "Mimpi Burubut" (1988), Sitti Rahman G. Ibrahim’s "Lapik Pinang" (1994), Kathrina Tahti’s "Sogit" (2000), Juri Durabi’s "Aur Sungai & Tebing" (2017) and Chacho Muhama’s "Atap Nipah" (2017)-the changing treatment of a particular recurring theme and characters in these stories will contribute to a better understanding of the development of Sabah Malay literature as part of a wider scope of Malaysian literature. The short story genre is selected based on the sustaining productivity of the selected authors and their technical contribution to the development of the particular genre. Apart from uncovering the development of Sabah Malay literature through a structural review of the selected short stories produced from the 1980s to the 2000s this research article exposes the social political influences that have shaped Sabah Malay literature in the development of Malay literature. Keyword: Sabah Malay Literature, Wadah, short stories 1980-2017, local colour